THE EFFECT OF ASCORBIC ACID ON THE QUALITY CHANGES OF TILAPIA ABON (Oreocromis niloticus) DURING ROOM TEMPERATURE STORAGE - Sari, Ira; ', Nurmalia; ', Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was carried out to evaluate the effect of ascorbic acid on quality changes of tilapia abon during room temperature storage. Tilapia weighing 400-600 g each was taken from a fish market in Pekanbaru. Three fish abons prepared from the fish meat were respectively added with ascorbic acid : 0% (A0), 2 g (A1) and 3 g (A2) of the fish weight. The fish abon were packed in HDPE plastic bag and kept at room temperature for 60 days. The quality changes were evaluated for sensory quality, moisture, fat, peroxide value and mould every 0, 30 and 60 days. The result indicated that the quality of A1 and A2 was more stable than that of A0. Both abons were still acceptable up to 60 day storage while A0 was rejected at 30 day storage. Peroxide value of the abon at initial to the end of storage was 1.68-10.62 meq/1000 g sample for A0, 0.78-7.96 meq/1000 g sample for A1 and 0.50-5.86 meq/1000 g sample for A2. Moisture at initial to the end of storage was 2.78-9.15% for A0, 2.96-6.12% for A1 and 3.08-7.97% for A2. Fat at initial to the end of storage was 24.19-3.89% for A0, 21.63-27.20% for A1 and 20.23-26.36% for A2.Keywords: Oreocromis niloticus, sorbic acid, tilapia abon, storage